Miasma, munskydd och mikrober: Epidemiologiskt tänkande genom århundradena - Dinu, Radu Harald (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2021)
This paper examines historical dimensions of face masks and other types of protective equipment used during epidemics. The author suggests that face masks neither can be reduced to their materiality nor studied as mere medical products aiming at forming a physical barrier against infectious diseases. As human artefacts, face masks have been interwoven with history and culture and thus reflect how social norms and ideas about a given social order have been negotiated throughout history. The paper suggests that face masks represented a measure of state authority and a symbolic reference to people’s hope to control infectious diseases. The examples studied in this paper include the plague in early modern Europe, the Manchurian plague, the Spanish flu, polio and HIV. The study is based on a literature review of published historical sources and recent research in the fields of epidemiology, medical sciences, and the history of ideas.